KEMUDAHAN MERENCANAKAN PEMBELAJARAN DENGAN MODEL KEMP - Haifa Farsya Nafisah; Sri Marmoah (JURNAL ILMIAH NUSANTARA, 2026)
Learning planning is highly dependent on the teacher who plans it. Teachers are the spearhead in this regard. Therefore, a teacher needs a learning planning model that is not rigid, uncomplicated, flexible, and easy to implement in the class. This article aims to discover the ease of the Kemp model that helps teachers in planning learning. This is an answer to the problems faced by most teachers. This research uses a literature study data collection method and a content analysis approach. The literature study method allows for the collection of various literature sources in the form of previous research relevant to the title. These literature sources are selected based on criteria. Appropriate literature is extracted for its main ideas, grouped, and processed or analyzed in the discussion. Then, the analysis produces comprehensive conclusions that are discussed in the conclusion section. Based on the literature that has been obtained, the Kemp model is a flexible model because its application is not limited to sequential steps. Therefore, using the Kemp model in learning planning will facilitate teachers in optimizing lesson plans. The conclusion of this study is that the Kemp model can facilitate and provide a solution for teachers in planning learning activities.